Bridging Theory and Practice: Implementing Hots Learning in Elementary Education - Taubah, Mufatihatut; Mailasari, Dewi Ulya (IKIP PGRI Bojonegoro, 2024)
This study investigates the implementation of higher-order thinking skills (HOTS)-based learning and assessment in an elementary school in Madura and the challenges teachers face in applying them. The study employs a qualitative field study approach with descriptive methods, utilizing observation, interviews, and documentation for data collection. Data analysis follows an interactive Model comprising data reduction, presentation, and conclusion drawing. The findings reveal that HOTS-based learning and assessment in Islamic Religious Education (PAI) have significant potential to develop students’ higher-order thinking skills by integrating applicable religious values. This approach enhances the cognitive, affective and psychomotor domains, resulting in meaningful religious education that impacts students’ daily lives. However, implementation is hindered by teachers’ limited understanding and technical expertise in constructing HOTS questions. To address this, training and support from relevant stakeholders are essential to enhance teacher competence in designing and implementing HOTS-based learning and assessment effectively.